The Impact of Corporate Income Tax on Asset-liability Ratio: An Empirical Study of Chinese Listed Companies - Junbo, Er (2022)
This paper examines the impact of corporate income tax on capital structure. 2014 saw the State Council issued "Several Opinions on Further Promoting the Healthy Development of the Capital Market" (referred to as the New Article 9), which made the following recommendations on corporate income tax: the scope of application of the policy of reducing corporate income tax by half for SMEs was expanded four times, from 30,000 yuan to 300,000 yuan in annual taxable income, and the corporate income tax rate was gradually increased from 25% to 12.5%. The corporate income tax rate was reduced by half from 25% to 12.5%. This situation fits well with the capital structure theory and is suitable for research. This paper reviews the research and development process of capital structure theory, sorting out the different theories, as well as the results of the theoretical and empirical studies. In the empirical analysis, this paper uses data from Chinese A-share listed companies over the period 2010-2020 to conduct an empirical study and formulate two hypotheses through a fixed effects model. The results find that a lower corporate income tax reduces the leverage and debt levels of companies and increases their cash and investment. For firms with different natures of ownership (SOEs and non-SOEs), the impact of the new Article 9 policy is larger for SOEs than for non-SOEs. This paper finds that the reduction in corporate income tax is conducive to corporate deleveraging, and in response to China's current leverage growth, the government can implement corporate income tax reduction policies to facilitate corporate deleveraging. Secondly, tax cuts for state-owned enterprises (SOEs) can be implemented to facilitate deleveraging, solve the problem of "zombie enterprises" and alleviate the soft budget constraint of local governments.